2020
DOI: 10.1038/s41419-020-03052-1
|View full text |Cite
|
Sign up to set email alerts
|

FATS regulates polyamine biosynthesis by promoting ODC degradation in an ERβ-dependent manner in non-small-cell lung cancer

Abstract: Polyamine biosynthesis is an essential metabolic pathway for cell growth and differentiation in non-small-cell lung cancer (NSCLC). Fragile-site associated tumour suppressor (FATS) is a novel gene involved in cancer. The results of our previous study showed that FATS-mediated polyubiquitination of p53 promotes the activation of p53 in response to DNA damage; however, little is known about the role of FATS in metabolic reprogramming in NSCLC. In the present study, FATS was observed to be significantly downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…It would have also been more informative if we had collected information on other biochemical and biological parameters of cellular metabolism. 32,33 Based on our results, we have highlighted the association between treatment-related toxicities and malnutrition, and the relevance of malnutrition on patient-reported QoL. As a next step, we hypothesized that active and timely nutritional intervention could mitigate the extent of malnutrition and reverse some of the impact on QoL.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It would have also been more informative if we had collected information on other biochemical and biological parameters of cellular metabolism. 32,33 Based on our results, we have highlighted the association between treatment-related toxicities and malnutrition, and the relevance of malnutrition on patient-reported QoL. As a next step, we hypothesized that active and timely nutritional intervention could mitigate the extent of malnutrition and reverse some of the impact on QoL.…”
Section: Discussionmentioning
confidence: 73%
“…Next, we acknowledge that WL is a crude surrogate of malnutrition, and other indicators such as sarcopenia (measured on scans) would be more representative of a patient's nutritional status. It would have also been more informative if we had collected information on other biochemical and biological parameters of cellular metabolism 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…A link between ERβ and autophagy in LC has been suggested by Qiu and co-workers in a recent study [121]. They observed that fragile-site associated tumor suppressor (FATS), a novel oncogene involved in LC, was significantly downregulated in NSCLC tissues compared with adjacent normal tissues and was associated with the survival of NSCLC patients.…”
Section: Lung Carcinomamentioning
confidence: 84%
“…FATS was shown to function as a suppressor of polyamine biosynthesis by inhibiting ornithine decarboxylase (ODC) at the protein and mRNA levels, and this mechanism was dependent on ERβ. In fact, FATS binds to ERβ and translocates to the cytosol, leading to ODC degradation [121].…”
Section: Lung Carcinomamentioning
confidence: 99%
“…While the role of rare fragile sites in tumors remains unclear, CFS is consistent for many tumor genome mutations, and they are closely related to the occurrence and development of tumors (9). The introns and expression regulatory regions of fragile-site associated tumor suppressor (FATS) gene are rich in AT repeat sequences and have characteristics of typical fragile locus genes (10). FATS is a tumor suppressor gene associated with DNA damage-induced tumors.…”
Section: Introductionmentioning
confidence: 99%